2016
DOI: 10.1021/acsami.6b05468
|View full text |Cite
|
Sign up to set email alerts
|

Study of Perovskite QD Down-Converted LEDs and Six-Color White LEDs for Future Displays with Excellent Color Performance

Abstract: A narrow-emitting red, green, and blue (RGB) perovskite quantum dot (PeQD)-based tricolored display system can widen the color gamut over the National Television System Committee (NTSC) to 120%, but this value is misleading with regard to the color perception of cyan and yellow reproduced in the narrow RGB spectra. We propose that a PeQD-based six-color display system can reproduce true-to-life spectral distributions with high fidelity, widen the color gamut, and close the cyan and yellow gap in the RGB tricol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(99 citation statements)
references
References 55 publications
3
96
0
Order By: Relevance
“…Here, the PL colors of the PeQDs can be blue-shifted by widening the bandgap through the formation of an alloy with smaller anions, decreasing both the unit cell and the covalency of the PeQDs. As we reported previously 1719 , six selected colors of fully down-converted LEDs were fabricated by capping a LPDF-capped LED package filled with PeQD/NOA 63 paste. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the PL colors of the PeQDs can be blue-shifted by widening the bandgap through the formation of an alloy with smaller anions, decreasing both the unit cell and the covalency of the PeQDs. As we reported previously 1719 , six selected colors of fully down-converted LEDs were fabricated by capping a LPDF-capped LED package filled with PeQD/NOA 63 paste. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently developed perovskite (Pe) QDs as well as Cd-containing II-VI QDs are excellent candidates for tunable multi-package WLEDs 1317 . Instead of using environmentally harmful, recently commercialized Cd-containing II-VI QDs, the PeQD family is becoming more popular as a less environmentally harmful and excellent candidate for maximizing the circadian tunable range and two-measure system of color quality levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the family of LHP materials, colloidal all-inorganic cesium lead halide (CsPbX 3 , X = Cl, Br, and I) perovskite nanocrystals combine both high stability and superior high luminescent efficiency compared to their organic-inorganic counterparts [18,19]. With their colloidal properties, many works have concentrated on applying them to solution-processed devices such as display screens [20], lasers [12] and LEDs [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the application of CsLHQDs has been found to be useful in display-related devices such as LEDs, and impressive progress has been made in this direction. 94,95 Song et al 80 fabricated the first quantum dot light emitting diode (QLED) based on CsPbX 3 QDs with the device configuration ITO/PEDOT: PSS/PVK/QDs/TPBi/LiF&Al. The authors observed luminances (i.e., the intensity of light emitted from a surface per unit area in a given direction) of 742, 946, and 528 cd m −2 (cd ¼ candela) with external quantum efficiency (EQE) values 0.07%, 0.12%, and 0.09% for the blue, green, and orange LEDs.…”
Section: Applications Of Cs-lhqdsmentioning
confidence: 99%